The importance of rapid assessment tools in evaluating mental health in emergency departments among patients with chronic diseases - Vallath, Aditya Lal; Sivasubramanian, Barath Prashanth; Ravikumar, Diviya Bharathi; Lalendran, Akshita; Krishnan, Suhasini; Samanta, Sudeshna; Banerjee, Snigda; Das, Tania; Kundu, Ritwick; Richharia, Vyom; More, Ravisha; Khithani, Mishika; et al. (Frontiers in Public Health, 2024)
Background: Rapid screening tools such as the WHO well-being Index (WWBI), Six-item screener (SIS), and the CLOX-1 test can be used to assess overall mental health and cognition respectively.We sought to evaluate mental health with cognition in individuals with chronic diseases and stable vital signs presenting to the Emergency Department (ED).Methods: An observational study in the ED with 279 participants was conducted.Results: Chronic diseases were more prevalent among 51-70 years (43.4%) and diabetes was most common (58.8%). Fever (22.6%) and GI bleeding (32.6%) presentation were high. Participants with low WWBI had low SIS compared to the ones with higher scores (83.3% vs 17.7%, p<0.001) and also had low CLOX-1 compared to ones with high CLOX-1 (67.3% vs 5%, <0.001). A positive correlation between WWBI with SIS (correlation coefficient=0.305, p<0.001) and CLOX-1 (0.441, <0.001). Regression analysis indicates a positive association between WWBI and the SIS (standardized regression coefficient=0.187, 95%CI= 0.236-1.426, and p=0.006) and CLOX 1 (0.338, 0.2-0.463, <0.001).In the ED, the evaluation of mental health even among cognitive impaired is feasible and crucial.